2020
DOI: 10.32725/kont.2020.040
|View full text |Cite
|
Sign up to set email alerts
|

The lived experience of Indonesian nurses in Kuwait: A phenomenological study

Abstract: Introduction: Indonesia is recognized as an active player in the sending of health professionals, including nurses, abroad. Indonesian nurses are also placed in Middle Eastern countries, such as Kuwait. Nevertheless, there is little research exploring the life experience of Indonesian nurses living and working in Kuwait. Methods: The design of this study was qualitative with a phenomenological approach. Participants in this study were 21 Indonesian nurses who have lived and worked in Kuwait for a minimum of on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Previous studies revealed that economic, career and social factors became motives of nurses working overseas, such as in Taiwan, Kuwait, Japan, Australia and the United States (Dahl et al., 2021; Efendi et al., 2016, 2020; Nursalam et al., 2020; Zhong et al., 2017). Nevertheless, in our study, although nurses are experiencing financial problems and only have limited career options, they chose to stay in Indonesia because they want to stay close to their husbands and children.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies revealed that economic, career and social factors became motives of nurses working overseas, such as in Taiwan, Kuwait, Japan, Australia and the United States (Dahl et al., 2021; Efendi et al., 2016, 2020; Nursalam et al., 2020; Zhong et al., 2017). Nevertheless, in our study, although nurses are experiencing financial problems and only have limited career options, they chose to stay in Indonesia because they want to stay close to their husbands and children.…”
Section: Discussionmentioning
confidence: 99%
“…The data illustrates the global demand for Indonesian nurses to utilise the opportunity to work in selected destination countries. Efendi et al (2016Efendi et al ( , 2020 reported factors that encourage nurses to leave Indonesia and find work overseas, including social, economic and career factors. Despite all of these push factors, Indonesian nurses who eventually work in other countries are still low, as reported by BNP2TKI (2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Difficulties in acculturation due to deep-rooted cultural beliefs upheld by Chinese [41], Indian [40,53] and Japanese migrant nurses [43] have been documented. Moreover, cultural distance-a collective term denoting differences in religious beliefs, ethnicity, social norms, and languages-predicts the Asian IENs' retention, as shown in four studies [31,35,44,52]. Nonetheless, some encouraging evidence has suggested that Asian IENs employed in Asian countries could acculturate more rapidly than those employed in non-Asian countries [31,35,44,52].…”
Section: Theme 4: Acculturationmentioning
confidence: 98%
“…The factors that motivated Asian IENs to migrate were economic, work-related, and personal. As for the first factor, seven studies emphasised the role of economic factors, citing nurses' desire to attain a better socio-economic position than that in their home country [30][31][32][33][34][35][36]. The specific reasons underlying the push factors for Asian IENs to leave their current host countries were the deteriorating exchange rate of the current host country [37], the unfair, discriminatory remuneration practices based on nationality [38], and the declining pay when compared with that in more affluent host countries [39].…”
Section: Theme 1: Desire For Better Career Prospectsmentioning
confidence: 99%